Life love lust a critical discourse analysisi on the realationship problem section of cosmopolitan - Segovia, Angela Carla L.; Sison, Raymund O.; Dr. Arcellana, Lydia R. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2005)
This study aims to reveal and understand how women view themselves and how such views affect gender relation's in the Philippine Society through their use of language in their letters to a section in cosmopolitan Philippines entitled Margie Holmes: life love lust. The letters are examined using Fairclough's Critical Discourse Analysis where the three stages of analysis- description, interpretation and explanation - are appropriated. An examination using Hallidayan transitivity system and Searle's Speech Act Theory serve as our description stage. By using such framework, it is found that women view themselves as subordinate to men. They see themselves in their traditional/conservative roles in the society as girlfriend/wife/mistress. They see themselves as submissive to their boyfriend/husband. In a relationship between man and woman, it is found that it is always the woman who cares so much about the relationship, and oftentimes, they are the ones left heart-broken. They consider the man in their lives as the most important component of their life, and when their relationship with that man collapses, their world collapses as well. With such images of themselves, women identify with these representations and feel negatively about themselves. They think that these roles are inherent in them therefore making it more difficult for them to get out of this kind of inequality. These patriarchal views of women on themselves help perpetuate gender inequality against women in the society, in as much as these views are created by the existing patriarchy in the society.
Thesis (Bachelor of Arts in English Studies: Language)--University of the Philippines Diliman
Includes bibliographical references (pages 102-103).